A complexity view on the future of work: Meta-modelling exploration of the multi-sector K+S agent based model - Giovanni Dosi; Marcelo C. Pereira; Andrea Roventini; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
When complexity meets economics, complexity economics turns out to be something more than simple interactions across individuals/entities, it turns into what has been labelled the bicycle postulate made of two components, coordination and change. Granted the ''Complex evolving system approach'', we provide an example of the effectiveness of the complexity view in economics applied to the context of the current debate on the future of work drawing upon the agent-based ''Schumpeter meeting Keynes'' multi-sector model (Dosi et al., 2022) and the meta-modelling approach developed in Dosi et al. (2018). The complexity approach proves to be an alternative, useful lens to address the technical change vs employment relationship modulated by demand patterns, income distribution, structural change and labour market organizations. It allows to enlarge the scope of investigation beyond production functions of tasks, relative prices of capital vs labour, inputs substitutability, comparative advantages of workers in their skill levels, the latter elements upon which the dominant neoclassical approach on the employment-technology nexus is rooted.
Keywords: J51; E02; E24; C63; 330; Complexity; Meta-modelling; Future of work